Anthropogenic influences on soil microbial properties - Menefee, Dorothy (Kansas State University, 2016)
Human activities have the potential to alter soil biochemical properties in a number of different ways. This thesis will focus on how agricultural practices (tillage and cropping system), climate change, and urban soil pollution (primarily lead and arsenic) affect soil biochemical properties. Two incubation studies were conducted to determine how human activities influence soil biochemical properties. The first study focused on how altered temperature and moisture regimes affected soil properties from four different agroecosystems. Four different soils were incubated under two different soil preparation methods (sieved <4mm and <0.25 mm), three different temperature treatments (12, 24, and 36°C), and two different moisture treatments (field capacity and 80% of field capacity) for 180 days. Destructive samples were taken at 7, 30, 60, 120, and 180 days and the soil microbial community was analyzed using phospholipid fatty acid analysis (PLFA). The second study investigated how soil amendment treatments (Mushroom Compost and Composted Biosolids) of an industrially contaminated site affected the biochemical properties of that soil. Surface soil samples collected 435 days after compost addition from urban garden test plots located adjacent to a former rail yard in Monon, Indiana. Soils were incubated for 30 days to stimulate microbial activity. Following incubation, the soil was analyzed for PLFA, soil enzymes, and available metal fractions. In the first study the greatest differences were found between the <4mm and the <0.25 mm size fractions – which highlights the effect of soil aggregation and structure on microbial populations. After aggregation effects, temperature treatment had the next largest effect on microbial populations, with the greatest biomass in the middle (24°C) treatment. The second study assessed different soil amendments on soil microbial properties and metal availability. Composted biosolids reduced metal availability and increased microbial enzyme activity and biomass.
Keywords: Soil microbiology; Climate change; Urban soils